Competitiveness in the invitation to bid for the concession of the urban bus system of the metropolitan region of Recife - Rolim, Fernando (2020)
This paper discusses aspects related to competitiveness in the Invitations to Bid (ITBs) of the public tender for the concession of the urban bus public transport services in the Metropolitan Region of Recife (RMR), in the Brazilian Northeastern Region. The bids were conducted by three different public bodies - the Municipalities of Recife and Olinda and the State of Pernambuco. Basic features of the bidding terms are presented and some of their aspects that have jeopardized competition are pointed out, notably the small number of lots, the lack of diversification of the size of lots, the possibility of forming consortia with unlimited number of participants, and the ownership of depots. Hence, some criticisms towards the bidding terms are stated and in order to prove the criticisms it is shown a simulation of an arrangement amongst incumbents, based on the rules of the tenders themselves, in which the allocation of potential winners ex post bidding does not differ from the ex ante scenario. Since the biddings have already been concluded and their results confirm the arrangement simulated, and since their winners have not proposed any amount bellow the reserve prices, the main conclusion is that competitiveness was put on the jeopardy